‎Пророкот Јона и проблемот на прифаќање на Божјото милосрдие - Ѓоко Ѓорѓевски (ПБФ „Свети Климент Охридски“ - Скопје, 2018)
To the story of Jonah is dedicated a small book of the Old Testament, formed of just four chapters, in which the parable of a prophet is narrated, when, against his will, God sends him to preach the conversion to the inhabitants of Nineveh, symbol of power, hostility and evil. The text of the analysis attempts to deepen and actualize the message of the book of Jonah, highlighting the greatness of God’s love and the universality of His salvation.